Fiscal Decentralization and Government Size in Latin America - Ernesto H. Stein (Inter-American Development Bank, Office of the Chief Economist, 1998)
Although the region remains highly centralized, the tendency toward decentralization is quite strong. Not only is a larger portion of the general government budget executed from the subnational government level, the autonomy that these governments have in deciding how much to spend and what to spend on is increasing as well. In this context, it is important to analyze the possible effects of the move toward decentralization on fiscal performance.
Keywords: 330